(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
In the article the species composition and diversity of lichens of Oleshkivski suburban sandy area are given. This site was founded as a farmstead in the late 1940’s – mid 1990’s and intensely used as garden and vegetable garden for agricultural products and for feeding animals. Since the mid-1990s a transformation of rural estates in suburban plot had begun. It takes place nowadays as well. There is a number of plant species that grow on sand. The territory of the kitchen-garden, the garden and the court is planted with weeds, perennial and annual flowers. Mosses and lichens settled at the planted trees and other substrates. Currently, there are 67 species of wild herbaceous plants, 12 species of aromatic, 77 species of flowers and ornamental plants and 44 species of vegetables. Trees, shrubs and climbing plants are presented by 69 species, bryophytes – by 17 species, lichenicolous mushrooms – by 1, lichens – by 18 species. Some representatives of the flora of Ukraine are indicated in the environmental documents.